An unusual presentation of ghost cell odontogenic carcinoma: A case report with review of literature - K Remya; S Sudha; Reshmi G Nair; H Jyothi (Wolters Kluwer Medknow Publications, 2018)
Ghost cell odontogenic carcinoma (GCOC) is a malignant odontogenic epithelial tumor which is an exceedingly rare, highly aggressive, rapidly growing, and infiltrative tumor forming the malignant counterpart of long-standing benign cystic lesions coming in the spectrum of calcifying odontogenic cysts. To date, only a few cases have been reported in the medical literature. A case of unusual presentation of GCOC is presented and the clinical, histopathological, and immunohistochemical features are discussed along with a literature review. Our case report further emphasizes the bizarre biological behavior of this tumor and the need for strict long-term surveillance of the patients as metastasis to distant sites has been reported.